HPTLC Analysis of Neem Oil Extract in Herbal Dosage Form - Mohamed Musthaba, S.; Athar, M.T.; Baboota, Sanjula; Ahmad, Sayeed (Asian Journal of Chemistry, 2010)
The aim of present study is to develop a simple, specific, accurate and reproducible TLC method for the quantitative estimation of neem oil extract in capsule/tablet dosage form. Chromatographic analysis was performed using Camag HPTLC system, in marketed herbal formulation of neem oil extract on precoated silica gel aluminium TLC plate 60F254 with a solvent system of chloroform:ethyl acetate containing 1 % acetic acid 8:2 (v/v) and detection was done by densitometric analysis at a wavelength of 265 nm without any derivatization. Samples of tablet and capsule formulation revealed peaks at the Rf 0.33 ± 0.02, 0.55 ± 0.02 (substance 1 and substance 2). The amount of substance in the sample was determined by using standard calibration curve which was found good linear in the range 4 μg to 100 μg with r2 0.9936 and 0.9931 (with respect to peak area) and r2 0.9931 and 0.9916 (with respect to peak height) of substance 1 and substance 2, respectively. The limit of detection (LOD) and limit of quantification (LOQ) were 1 μg and 4 μg, respectively for both substances.